In Vitro Antimicrobial Activity of Tigecycline - Bhatta, Sabita; Basu, Babli; Chaudhary, Chandrasekhar Narharrao; Praharaj, Ashok Kumar (Medical Journal of Shree Birendra Hospital, 2015)
Introduction: Tigecycline is a novel glycylcycline  derivative of the tetracycline with activity against a wide range of  organisms including Methicillin resistant Staphylococcus aureus, Vancomycin  resistant  Enterococcus , Extended spectrum beta lactamase   producing  (Escherichia coli , Klebsiella  pneumonia)  and Acinetobacter species.  The aim of the study was to assess effectiveness of the drug against methicillin resistant Staphylococcus aureus (MRSA), vancomycin resistant enterococci (VRE), ESBL producers and carbapenem resistant Acinetobacter baumannii and to compare the efficacy of different methods of antimicrobial susceptibility testing for Tigecycline.Methods: A total of 250 clinical isolates were processed and identified by conventional methods. In all the 250 isolates, antimicrobial susceptibility was carried out by disc diffusion method , Minimum inhibitory test by agar dilution method (MIC) and in 30 isolates of A baumannii  MIC was also done by E test.Results: Out of 250 isolates, 236 isolates were sensitive to tigecycline by agar dilution method while only 159 were sensitive by disk diffusion method.Conclusion: Marked discordance was observed between the results of two different methods (DDT & Agar dilution method) for E coli, Klebsiella spp and A baumannii, where significant number of isolates were resistant to tigecycline by DDT as compared to AD method. But results of MIC by agar dilution method & E test were in concordance for A. baumannii.